Mortality and complications after prostate biopsy in the Prostate, Lung, Colorectal and Ovarian Cancer Screening (PLCO) trial. (21st November 2013) - Pinsky, Paul F.; Parnes, Howard L.; Andriole, Gerald
Abstract : Objective: To examine mortality and morbidity after prostate biopsy in the intervention arm of the Prostate, Lung, Colorectal and Ovarian Cancer Screening (PLCO) trial. Subjects and Methods: Abstractors from the PLCO trial recorded the types and dates of diagnostic follow‐up procedures after positive screens and documented the types and dates of resultant complications. Cancers and deaths among the participants were tracked. The mortality rate in the 120‐day period after prostate biopsy was compared with a control rate of deaths in the 120‐day period after a negative screen in men without biopsy. Multivariate analysis was performed to control for potential confounders, including age, comorbidities and smoking. Rates of any complication, infectious and non‐infectious complications were computed among men with a negative biopsy. Multivariate analysis was used to examine the risk factors for complications. Results: Of the 37 345 men enrolled in the PLCO trial (intervention arm), 4861 had at least one biopsy after a positive screen and 28 661 had a negative screen and no biopsy. The 120‐day mortality rate after biopsy was 0.95 (per 1000), compared with the control group rate of 1.8; the multivariate relative risk was 0.49 (95% CI: 0.2–1.1). Among 3706 negative biopsies, the rates (per 1000) of any complication, infectious and non‐infections complications were 20.2, 7.8 and 13.0, respectively. A history of prostate enlargement or inflammation was significantly associated with higher rates of both infectious (odds ratio [OR] = 3.7) and non‐infectious (OR = 2.2) complications. Black race was associated with a higher infectious complications rate (OR = 7.1) and repeat biopsy was associated with lower rates of non‐infectious complications (OR = 0.3). Conclusion: Mortality rates were not found to be higher after prostate biopsy in the PLCO trial and complications were relatively infrequent, with several risk factors identified.